An analysis of minority people persecuted by their own government and ruling people - Abdullah @ Chuah Hock Leng, Osman (Elixir International Journal, 2016)
This article is about the unending pain of an minority ethnic group deprived of citizenship by the majority ruling class of the nation. It has no citizenship rights in their own nation. The man of this ethnic minority group has to work with no pay but with their own food a day a week for the dominated power. This ethnic group has no birth rights even to travel in their nation. They have to apply to travel with certain dates and must go back in the date otherwise they would not be able to return to the place they live even this is the place they are born. If they want to get marry, they have to apply to the local government to do so but it takes about six to seven years to get the approval. After getting the approval, they are not allowed to have more than two children. They are not allowed to work under the public services. … They are deprived of all means to live. This is the ethnic group known as Rohingyai in Myanmar.